The caregiver's experience of childhood cancer treatment in South Africa - I. R. Joosse; H. A. van den Ham; A. K. Mantel-Teeuwisse; F. Suleman (Taylor & Francis Group, 2024)
ABSTRACTBackground This study explored the treatment-related, financial and psychological experiences of caregivers during cancer treatment of their children in South Africa's (SA) public and private sectors.Methods In this exploratory study, three focus groups were conducted with caregivers of children undergoing cancer treatment in SA's public healthcare sector. A fourth small focus group with two parents in the private sector was conducted online. A mixed-methods approach was employed using a combination of thematic analysis and grounded theory.Results Of the 20 public sector caregivers, many expressed frustration at the number of visits to primary healthcare clinics before being referred. Caregivers had difficulties coping with and accepting the diagnosis, alongside managing continued care for the child and other children at home. Support received by family and community members was varied. Financial strain was an important concern. The two private sector parents indicated greater levels of support and no financial hardship, but expressed similar levels of emotional stress.Conclusion These caregiver experiences indicate that improvements are urgently needed in the recognition of childhood cancer symptoms at primary healthcare level in SA. They also highlight a need for increased financial support from government through social grants, travel allowances and nutritional support.